2024
DOI: 10.1002/adfm.202401353
|View full text |Cite
|
Sign up to set email alerts
|

Perylenedioic Acid‐Derived Carbon Dots with Near 100% Quantum Yield in Aqueous Solution for Lasing and Lighting

Yupeng Liu,
Bingzhe Wang,
Yunsen Zhang
et al.

Abstract: Carbon dots (CDs) are a burgeoning star of luminescent carbon‐based nanomaterials with emerging interest for various applications. Luminescence from the sp2‐conjugated domains in the carbon cores is considered to be the intrinsic bandgap emission of CDs, whereas the relationship between them remains poorly understood. Simultaneously, the solvent relaxation of water molecules will quench the fluorescence of CDs, thus, obtaining strong luminescence from CDs aqueous solutions remains a great challenge. Herein, a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 56 publications
1
4
0
Order By: Relevance
“…Figure S7B further elucidates the structural features of B-CDs, exhibiting clear −O–CO signals between 160 and 180 ppm. These aromatic carbon resonances can be observed from 120 to 140 ppm . These spectral findings, in conjunction with mass spectrometry and NMR data, robustly endorse the hypothesized model structure denoted as “6–5c”.…”
Section: Resultssupporting
confidence: 68%
“…Figure S7B further elucidates the structural features of B-CDs, exhibiting clear −O–CO signals between 160 and 180 ppm. These aromatic carbon resonances can be observed from 120 to 140 ppm . These spectral findings, in conjunction with mass spectrometry and NMR data, robustly endorse the hypothesized model structure denoted as “6–5c”.…”
Section: Resultssupporting
confidence: 68%
“…17,18 Therefore, they have been widely studied and initially applied in the fields of biomedicine, sensing, and energy conversion/storage. 19,20 Furthermore, the small size, spherical structure, high specific surface area, and eco-friendly of CDs make them suitable for lubricant additives in the field of tribology. 5,21 Liu et al 22 synthesized N-doped carbon quantum dots (CQDs) via onepot pyrolysis of citric acid.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Berman et al demonstrated that macroscopic superlubricity occurred between the hydrogenated diamond-like carbon surface and the onion-like carbon structures (OLCs), with a very low coefficient of friction (COF) reaching 0.005 . As a new zero-dimensional (0D) carbon nanomaterial, carbon dots (CDs) are spherical or quasi-spherical carbon nanomaterials with sizes less than 10 nm. , CDs usually have sp 2 -hybridized conjugated nanonuclei, and their surfaces contain a large number of polar oxygen-containing groups such as hydroxyl (−OH) and carboxyl (−COOH), which makes CDs easily soluble in polar organic solvents. , Distinctive structures endow CDs with many attractions, such as high specific surface area, stable chemical/optical properties, excellent catalytic performance, low toxicity, and good biocompatibility. , Therefore, they have been widely studied and initially applied in the fields of biomedicine, sensing, and energy conversion/storage. , Furthermore, the small size, spherical structure, high specific surface area, and eco-friendly of CDs make them suitable for lubricant additives in the field of tribology. , Liu et al synthesized N-doped carbon quantum dots (CQDs) via one-pot pyrolysis of citric acid. The as-obtained N-doped CQDs had long-term dispersion stability (about 6 months) as additives of PEG and exhibited excellent antioxidant, antiwear, and friction-reducing properties.…”
Section: Introductionmentioning
confidence: 99%
“…[11a] Recently, we developed a straightforward method involving the thermal treatment of a perylene derivative in solid-melting boric acid to prepare CDs with nearunity photoluminescence quantum yields (PLQY) in aqueous solution. [14] Inspired by these, we conducted the thermal treatment of levofloxacin in solid-melting boric acid under ambient pressure. The crude product of CDs and boric acid complex (CDs@BA) exhibited RTP-TADF dual-mode afterglow.…”
Section: Introductionmentioning
confidence: 99%